Attribution of Works by Vladimir Grinberg and Alexander Vedernikov: The Problem of the Artist’s Signature - Alexandra Ivanovna Strukova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2021)
This article considers the phenomenon of the authors’ signatures of Vladimir Grinberg (1896—1942) and Alexander Vedernikov (1898—1975), two representatives of the Leningrad Landscape School community in the 1930s—1940s. During this period, they entered a single circle of friendly and professional communication and experienced mutual influences. The artists’ work is considered more broadly and goes beyond their participation in the community.